Clindamycin suppresses virulence expression in inducible clindamycin-resistant Staphylococcus aureus strains - Elisabeth Hodille; Cédric Badiou; Caroline Bouveyron; Michèle Bes; Anne Tristan; François Vandenesch; Gérard Lina; Oana Dumitrescu (BMC, 2018)
Abstract Clindamycin is a protein synthesis inhibitory agent that has the ability to suppress the expression of virulence factors in Staphylococcus aureus. Recent guidelines recommend the use of clindamycin for the treatment of toxin-mediated infections. Clindamycin modulates virulence expression at sub-inhibitory concentrations (sub-MICs) in clindamycin-susceptible S. aureus strains but previous report shown that this effect was supressed for constitutive clindamycin resistant strains. However, no data are currently available on the impact of clindamycin at sub-MICs on the virulence of inducible clindamycin-resistant S. aureus strains. Here, we show that sub-MICs of clindamycin decrease Panton-Valentine leucocidin, toxic-shock-staphylococcal toxin (TSST-1) and alpha-haemolysin (Hla) expression in six inducible clindamycin-resistant isolates cultivated in vitro in CCY medium. These results suggest that the clindamycin anti-toxin effect is retained for inducible clindamycin-resistant S. aureus isolates; therefore, its usage should be considered within the treatment regimen of toxin related infections for inducible clindamycin-resistant S. aureus.